Considerations on the use of solid material for high performance, tubular linear motors - Mohammed, Ahmed M. (2017)
The last few decades have seen a considerable amount of research and development effort dedicated to linear machines. An important family of linear machines is the tubular, permanent magnet synchronous motor. As for any other machine, such motors are usually developed with laminated cores aimed at reducing core losses. However, for tubular machines, such a configuration requires cores laminated in the axial direction, making for quite expensive and time-consuming manufacturing processes. To address this aspect, this thesis proposes and investigates the use of solid materials for the core structure of the stator of a tubular machine. The journey to achieve this goal is presented in this thesis. It is shown how through the use of new material characterisation techniques (critical for understanding and modelling structures operating in unconventional magnetic circuits) and new eddy current reduction methods (proposed and validated on representative samples), excellent results in terms of manufacturing costs can be achieved without compromising a machine’s performance. A bench-mark machine comprising a laminated stator is analysed and detailed in the first part of the thesis. The work shows how an equivalent or even better motor (in terms of force density and performance) can be achieved while utilizing a solid material for its stator.